The Effect of Presowing Treatments on the Germination of Seeds of Two Savannah Tree Legumes - Agboola, D. A.; Ebofin, A. O.; Aduradola, A. M.; Ajiboye, A. A. (Indian Forester, 2005)
The effect of some presowing treatments on the germination of seeds of Albizia lebbek (Linn.) Benth. and Cassia siamea Lam., two savannah tree legumes in Nigeria were investigated. Percentage germination in fresh seeds was 15-25%, with 90-100% viability. The percentage germination in pretreated seeds ranged between 60-100%. The seeds of the two species exhibit physical dormancy due to hard seed coat. Dormancy in A. lebbek and C. siamea was terminated by soaking of seeds in concentrated suphuric acid for 10 and 15 minutes; wet heat at 100Â°C for 30 and 60 seconds; dry heat at 80-100Â°C for 5 to 10 minutes respectively. The percentage germination of seeds in the two species ranged between 90-100% after presowing treatments. Total carbohydrate and ethanol soluble sugars are well mobilized.